Mugil setosus Gilbert 1892 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Mugil setosus Gilbert, 1892. Liseta Mullet. Because the previous reported maximum length record, 91 cm (15.8 in) TL (McEachran and Fechhelm 1998), likely represents Mugil curema, the maximum size of this species is unclear. The largest specimen in the Scripps Institution of Oceanography Fish Collection is 39 cm (15.4 in) SL. Mission Creek, Santa Barbara County, southern California (Camm Swift, pers. comm. to M.L.) to Chile (Harrison in Fischer et al. 1995), including Gulf of California (Robertson and Allen 2002), and Islas Galápagos (Grove and Lavenberg 1997). Shallow marine, brackish, and fresh waters (Harrison in Fischer et al. 1995, Argulo et al. 2020); depth: surface (nightlight; Personal communication: Scripps Institution of Oceanography Fish Collection, La Jolla, California), intertidal to 25 m (82 ft) (min.: Thomson and Lehner 1976; max.: Amezcua Linares 1996). We note that Britzke et al. (2019) determined that fish identified as “ Mugil curema Valenciennes, 1836 ” from the eastern Pacific are, in ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 92, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...